Identification of the transneuronal homeostatic machinery at a central synapse - Harrell, E; Evan Harrell (2014)
Two different kinds of stabilising homeostatic behaviour have been observed in neurons. The first type involves the cell-autonomous maintenance of a cell-identity-based level of electrical activity. Neurons continually monitor their own electrical activity and can adjust many intracellular parameters, such as membrane ion channel densities, to keep this activity within a tight physiological range. The second type of homeostatic behaviour shares the same goal, to maintain a fixed level of electrical activity, but instead of adjusting intracellular parameters, the neuron recruits its synaptic partners to assist in maintaining a genetically prescribed activity level. This behaviour is most easily observed when a neuron is either electrically silenced by expressing an inwardly-rectifying potassium channel or rendered less sensitive to neurotransmitter through mutation of its postsynaptic receptors. Both of these perturbations result in increased synaptic drive from the presynaptic cells, either through increasing the number of neurotransmitter release sites or increasing the probability of release from single release sites. Many genes that are instrumental in the second type of homeostatic behaviour have been identified, mainly at the neuromuscular junction in the peripheral nervous system. However, studies on transsynaptic homeostatic compensation in an intact central nervous system have been few and far between. Also, which, if any, of the homeostatic genes are transcriptionally regulated in the nucleus after the onset of transsynaptic homeostatic adjustment, has not been adequately addressed. This thesis has developed a system to measure transcriptome-wide gene expression levels in presynaptic circuit elements after altering the firing properties of the downstream circuit in the CNS. Many transcriptionally regulated genes have been identified and are now being tested for their potential use as reporters for transsynaptic transcriptional regulation. It might be possible to capitalise on endogenous homeostatic signalling pathways to gain genetic access to synaptically connected neurons.